2012
DOI: 10.1111/j.1365-2141.2012.09169.x
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab before splenectomy in adults with primary idiopathic thrombocytopenic purpura: a meta‐analysis

Abstract: SummaryPrimary immune thrombocytopenia (ITP) is an acquired immune-mediated disorder with absence of any underlying cause. Corticosteroids are the standard initial treatment. Splenectomy is the main second-line treatment. A trend to delay or avoid splenectomy has developed thanks to new agents like rituximab. Few studies have assessed the response rate to rituximab in chronic ITP. We performed the first meta-analysis of randomized clinical trials and observational studies on rituximab as an effective splenecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 47 publications
6
54
1
3
Order By: Relevance
“…This intense B cell response and considerable expansion of shortlived PB in spleen is thus a hallmark of the disease. Rituximab-induced B cell depletion therapy is widely used in autoimmune diseases, and, accordingly, around 40% of patients with ITP respond to this therapy after 1 year (13) and 20% of them have a long-lasting response (14,15). This rate of response underlines the efficacy of the rituximab treatment, being able to totally block the ongoing production of ASC by proliferating GCs and memory B cells within lymphoid tissues (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This intense B cell response and considerable expansion of shortlived PB in spleen is thus a hallmark of the disease. Rituximab-induced B cell depletion therapy is widely used in autoimmune diseases, and, accordingly, around 40% of patients with ITP respond to this therapy after 1 year (13) and 20% of them have a long-lasting response (14,15). This rate of response underlines the efficacy of the rituximab treatment, being able to totally block the ongoing production of ASC by proliferating GCs and memory B cells within lymphoid tissues (20).…”
Section: Discussionmentioning
confidence: 99%
“…Around 40% of patients with ITP have an initial significant response to the anti-CD20 (rituximab) treatment (13) and 20% have a long-lasting (5 years and more) response (14). Among the remaining patients, who do not respond or have a transient response to rituximab, 60%-70% are cured by splenectomy (13)(14)(15). While reports agree on the efficient peripheral B cell depletion achieved by rituximab treatment, much less is known about B cell depletion in lymphoid tissues and the nature of the resistant pathogenic cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that younger age was associated with better response (Khellaf et al, 2014). A meta-analysis of studies of non-splenectomized patients receiving rituximab confirmed that younger age was the most relevant predictive factor of response in multivariate analysis (Auger et al, 2012). Rituximab may be associated with better response in the early stages of the disease (Khellaf et al, 2014).…”
Section: Rituximabmentioning
confidence: 93%
“…Rituximab in ITP leads to an overall initial response rate of 60%, and 30-40% after 2 years of follow-up (Arnold et al, 2007;Godeau et al, 2008;Auger et al, 2012;Khellaf et al, 2014). It has been reported that younger age was associated with better response (Khellaf et al, 2014).…”
Section: Rituximabmentioning
confidence: 99%
“…In France, based on the findings of a single-arm prospective study [4], RTX is now commonly used in persistent or chronic cases of adult ITP prior to splenectomy. Approximately 40-50% of patients treated with RTX at a standard dose achieve a complete response (CR) by 1 year [5] and 20% have a lasting response at 5 years [6]. The mechanisms of action of RTX to treat ITP remain speculative, although the removal of autoreactive B-cells is likely to play an important role.…”
Section: Introductionmentioning
confidence: 99%